SELF MANAGEMENT PROGRAM OF CLIENT WITH ARTRITIS LITERATURE REVIEW - Hesti Platini (LPPM Universitas Bakti Tunas Husada, 2018)
Osteoarthritis is a chronic disease that is common in the elderly and may recur and take place so that it can lead to progressive joint destruction during the client does not maintain regular lifestyle. Hence the need for an integrated program such as Self-Management that involves the client in arthritis management, decisions on the handling and treatment, so that the client actively participate in the management of the disease.The purpose of this literature review is to explain to the client's self-management of arthritis based on scientific research journal literature sources related.The method used in the writing of this literature review is surf the internet from Proquest databases, Google Scholar, Medscape and EBSCO using keywords Self-Management of, programs, and arthritis. Data were obtained, systematically arranged and conducted a discussion.Self-Management of the program is an effective way to prevent a decrease in motor activity and physical disability in the elderly, especially the client, so the client can improve the quality of life better. Advanced research related to self-management program on the client arthritis and community-based services can be applied to this program in Indonesia in particular